MEDIA QUIZIZ DALAM PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DAN LITERASI INFORMASI PADA PEMBELAJARAN PAI - Muhammad Akbar; Ahmad Yusron Hafidzi; Muhammad Jaelani (Maharah: Journal of Islamic Education Teaching and Learning, 2025)
This research is motivated by the importance of mastering critical thinking and information literacy skills in 21st century learning, especially in Islamic Religious Education (PAI) subjects. The purpose of this study is to explore the role of the digital media application Quizizz in improving both skills at SMAN 1 Selong. This study uses a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study show that Quizizz is able to stimulate students to think critically through analysis-based and evaluation questions. In addition, this application also helps improve information literacy skills, especially in identifying, evaluating, and using information effectively. Students showed high enthusiasm for the use of this media because the learning atmosphere became more interactive and enjoyable. This study concludes that the integration of digital media such as Quizizz in PAI learning can make a positive contribution to improving the quality of the teaching and learning process and equip students with essential skills in facing the challenges of the digital information society.